Cellular Homeostasis and Antioxidant Response in Epithelial HT29 Cells on Titania Nanotube Arrays Surface - SMN Mydin, Rabiatul Basria; Sreekantan, Srimala; Hazan, Roshasnorlyza; Farid Wajidi, Mustafa Fadzil; Mat, Ishak (Hindawi Publishing Corporation, 2017)
Cell growth and proliferative activities on titania nanotube arrays (TNA) have raised alerts on genotoxicity risk. Present toxicogenomic approach focused on epithelial HT29 cells with TNA surface. Fledgling cell-TNA interaction has triggered G0/G1 cell cycle arrests and initiatesDNA damage surveillance checkpoint, which possibly indicated the cellular stress stimuli. A profound gene regulation was observed to be involved in cellular growth and survival signals such as p53 and AKT expressions. Interestingly, the activation of redox regulator pathways (antioxidant defense) was observed through the cascade interactions of GADD45, MYC, CHECK1, and ATR genes.These mechanisms furnish to protect DNA during cellular division from an oxidative challenge, set in motion with XRRC5 and RAD50 genes for DNA damage and repair activities. The cell fate decision on TNA-nanoenvironment has been reported to possibly regulate proliferative activities via expression of p27 and BCL2 tumor suppressor proteins, cogent with SKP2 and BCL2 oncogenic proteins suppression. Findings suggested that epithelial HT29 cells on the surface of TNA may have a positive regulation via cell-homeostasis mechanisms: a careful circadian orchestration between cell proliferation, survival, and death. This nanomolecular knowledge could be beneficial for advanced medical applications such as in nanomedicine and nanotherapeutics.